1994
DOI: 10.1002/clc.4960170407
|View full text |Cite
|
Sign up to set email alerts
|

High frequency qrs electrocardiography in the detection of reperfusion following thrombolytic therapy

Abstract: Summary:The hypothesis that an increase in the amplitude (root-mean-square voltage) of the high frequency ( 150-250 Hz) components of the QRS complex occurs with successful reperfusion following thrombolytic therapy in acute myocardial infarction (AMI) and fails to occur when thrombolysis fails was tested. Clinical markers for successful or failed reperfusion following thrombolytic therapy for AM1 are notoriously insensitive. The amplitude of the high-frequency components of'the QRS complex decreases during is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Previous studies have indicated that reperfusion in patients with acute MI is accompanied by an increase in HF-QRS (15,16). The results of the present study support these previous findings.…”
Section: Comparison Between Standard and High-frequency Ecgsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have indicated that reperfusion in patients with acute MI is accompanied by an increase in HF-QRS (15,16). The results of the present study support these previous findings.…”
Section: Comparison Between Standard and High-frequency Ecgsupporting
confidence: 92%
“…The criterion described by Dissmann et al was used for the STsegment analysis: an ST-elevation resolution ≥ 50% after 1 hour of therapy was taken as an indication of early reperfusion (22). A change in HF-QRS exceeding 0.6 µV was considered significant (15). These cut-off values were also used for the comparison after 2 and 4 hours of recording.…”
Section: Ecg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these changes are considered to represent already necrotic areas (Q waves), but other, potentially reversible changes in the QRS complex also appear, although they are less well understood and are usually not considered for clinical decision making. Earlier studies on depolarization changes during ischemia due to acute coronary occlusion have considered QRS prolongation (1)(2)(3)(4)(5), amplitude changes of the R-and S-waves (4,6,7), "distortion" of the terminal part of the QRS complex (8)(9)(10)(11)(12) as well as changes in the high-frequency components of the QRS complex (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…These ischemia-related depolarization changes in the ECG are difficult to appreciate in time domain, but produce potentials with frequency content ranging from 40 to 250 Hz. Changes in this range have been demonstrated in various models of ischemia in preclinical and clinical settings[411]. However, the mode of detection, magnitude, direction, and frequency range of these changes have varied widely depending on the experimental and clinical conditions, with much attention devoted to the diminution of potentials seen using HFQRS analysis (in the range above 140 Hz)[12].…”
Section: Introductionmentioning
confidence: 99%